MIL‑125‑NH2/MIL‑88‑NH2 composite as a dual‑function adsorbent with enhanced photocatalytic and photo‑Fenton‑like behavior for the removal of organic pollutant in water - Wei Yee Low; Fuei Pien Chee; Norini Tahir; Nur Amira Solehah Pungut; Mohd Hafiz Abd Majid; Rachel Fran Mansa; Siow Hwa Teo; Pak Yan Moh (Springer Nature, 2025)
Metal–organic frameworks are nanoporous materials extensively studied for post-synthesis modification due to their exceptional adsorption and photocatalytic properties. However, their practical application is often limited by rapid electron–hole recombination, suboptimal band gap energies, and poor chemical and physical stability, limiting their reusability as adsorbents or photocatalysts. In this study, a novel Z-scheme MIL-125-NH2/MIL-88-NH2 composite was synthesized via reflux heating method. The composite demonstrated improved thermal stability compared to MIL-125-NH2 and a higher surface area than MIL-88-NH2, improving the physical and chemical properties. It selectively adsorbed cationic pollutants, following Langmuir isotherm with monolayer adsorption and physisorption mechanisms achieving a maximum adsorption capacity of 249 mg/g towards methylene blue (MB). Photocatalytic degradation of MB under visible and UV-A light irradiation reached 61% (k1 = 0.0067 min−1) and 69% (k1 = 0.0087 min−1), respectively. The addition of 1 mM hydrogen peroxide (H2O2), tripling MB removal to 89% removal (k1 = 0.0155 min−1) under visible light and 94% removal (k1 = 0.0217 min−1) under UV-A light. The synergistic effect of MIL-125-NH2/MIL-88-NH2 composite surpassed MIL-125-NH2/H2O2/UV-A (k1 = 0.0024 min−1) and MIL-88-NH2/H2O2/UV-A (k1 = 0.0150 min−1). Scavenger experiments identified hole (h+) and electron (e−) were the primary active species while hydroxyl radical (·OH) and superoxide (·O2−) also played key roles, with their generation further amplified by H2O2. These findings demonstrate the enhanced photocatalytic performance of the MIL-125-NH2/MIL-88-NH2 composite, attributed to its Z-scheme heterojunction structure and photo-Fenton-like behavior. The composite exhibits a promising stability and capability in advanced water treatment applications.